Study of Post-Natural Disaster Management Policy Implementation in Palu City: A Grindle Theory Approach to Policy Content - Muchtar, Ilham Muchtar Bin; Riadi, Slamet; Hasbullah, Hasbullah (Journal of Asian Multicultural Research for Social Sciences Study, 2023)
This research aims to examine the implementation of post-natural disaster management policies in Palu City by applying Grindle's theoretical approach to policy content. Palu City, as a disaster-prone area, has a history that underlies the urgency of this research. A qualitative approach with non-probability sampling techniques is used to understand in more depth the dynamics and complexity of post-disaster management policies. Primary data was obtained through in-depth interviews with informants selected purposefully, including affected residents, government institutions, and related non-government organizations. The research results highlight various aspects of the implementation of post-disaster management policies in Palu City. Constraints in land acquisition and budget limitations are the main challenges. Data analysis through Grindle's theoretical approach reveals the importance of considering policy content, such as the types of benefits produced and desired changes, as well as the policy context, including the roles and interests of the actors involved. This research also includes an evaluation of community perceptions of the policy and their level of participation in its implementation. By considering theoretical and practical aspects, this research provides a solid foundation for recommending more effective policy improvements focused on meeting the needs of affected communities and improving disaster preparedness and management in the future. Finally, this research has important implications for making policies that are more adaptive and responsive to the local disaster context and community aspirations.